Analysis of University Teaching Building Safety Based on Pathfinder Simulation - 장원원; 공하성 (International Journal of Advanced Culture Technology(IJACT), 2024)
This study systematically analyzes the evacuation safety of university lecture buildings. With the continuous improvement of educational facilities and the increase in campus population density, the efficiency and safety of evacuations in emergency situations have become critical issues for lecture buildings. Using Pathfinder software, this study models and simulates various evacuation scenarios to investigate the impact of architectural design parameters (such as stair width and emergency exit width) on evacuation times. Through three distinct evacuation scenarios, it was found that increasing stair width significantly reduces evacuation time, thereby enhancing evacuation efficiency. Although moderately widening emergency exits has a limited effect on evacuation time, it plays a positive role in alleviating congestion during evacuation processes. Moreover, a comparison between the simulation results and empirical formula calculations shows strong alignment, validating the model's practical applicability and accuracy. This research provides a scientific basis for fire evacuation design in university lecture buildings, recommending that stair and exit width optimizations be prioritized in building design and renovation. Future studies could further incorporate dynamic emergency scenarios, such as fires and earthquakes, combined with individual behavioral and psychological factors, to support the optimization of efficient evacuation strategies in complex environments.